Uso de geotecnologia para o mapeamento do município de São Francisco de Assis - RS - Pires, Rudineli de Bairros (2006)
Considering the diversity of elaborated software for the use of the Geoinformation Technology and the many kinds of cartographic and topographic documents related to Geoprocessing, this study mainly aimed at identifying correlations and different approaches among the programs that enable the analysis and the monitoring of spatial differentiations. Methodologically, the steps that guided the research were the following: a) the use of digital devices such as Spring 4.1.2; Arc View GIS 3.2.A.; Envi 4.0; Idrisi 32 Release Two; Adobe Photoshop 5.5; the use of cartographic documents as the Topographic Map; Image from the LandSat ETM+7 Satellite, 345/RGB bands and SRTM Image obtained from Labgeo/UFRGS. The results showed that the Adobe Photoshop program was distinguished in the steps of editing, assembling and in the treatment of images; Arc View GIS in layouts and systematic maps; Spring showed a better performance with the pure and treated SRTM Image, besides the LandSat Image, as well as in the generation of profiles and isolines; Idrisi was more efficient in the georeferring of maps and topographic maps while Envi had a satisfactory performance with SRTM standards for flight generation. This way, it is concluded that the researcher must know the different kinds of software that are available in the market, so that he/she may use, in the best way, the geotechnologies, always that it is needed to relate and correlate mappings in different units of study.